PENERAPAN SISTEM MANAJEMEN KESELAMATAN KONSTRUKSI PEKERJAAN BORED PILE PROYEK FASILITAS PERKERETAAPIAN - Kartika Hapsari; Trias Wiriyanto (Jurnal Ilmiah Teknologi Infomasi Terapan, 2022)
The Railway Facility Development Project has a large potential for work risk. This project certainly requires the implementation of a good SMKK so that zero accident can be achieved. The project is still experiencing a near miss (potential to cause) work accidents, one of which is in bored pile work. The purpose of this study is to find out how the implementation of SMKK is and what are the main inhibiting factors for the implementation of SMKK and the level of risk at the bored pile work stage, which refers to the assessment of the PUPR Ministerial Regulation No. 10 of 2021. Data collection is done by means of observation, questionnaires, interviews. Observations were made to collect data on the application of SMKK directly at the research location, and interviews to obtain data that had not been found during observations. Then the questionnaire data was taken to 23 respondents to get the main inhibiting factors in the implementation of SMKK. The results of observations and analysis of the implementation of SMKK are obtained with satisfactory results and the main inhibiting factor in the implementation of SMKK is the limited budget (K3). The assessment of the implementation of SMKK on the 5 elements of SMKK in the PUPR Ministerial Regulation No. 10 of 2021 was obtained at 87%, of which there were 2 elements that did not meet, namely the elements of leadership and work participation in work safety and construction safety support. The stages of bored pile work include safe work because the greatest risk is in the medium category.